Analysis of the effect of high falling water on the performance of hydroelectric power plants using whirpool type turbines - Mhd. Dimas Kurniawan; Etanto Heiliano Wijayanto; Siswo Pranoto; Indra Hermawan; Muhammad Idris (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
A hydroelectric power plant (PLTA) uses the flow of water as a source of energy. Evaluating the output of hydropower facilities, including the optimal height of the waterfall, turbine torque, electrical power, generator power, and generated efficiency, was the aim of the study. This study intends to investigate the power, torque, and efficiency that may be produced by a hydroelectric power plant with a whirlpool-type turbine, as well as how the height of falling water influences the operation of the plant. The experiment in this study measures three different waterfall heights with five different blade configurations. The study on the hydropower prototype involved three trials that collected data on torque, power, efficiency, waterfall height, and water discharge. The PLTA Prototype's best potential head in Test 3 was determined to be 0.01143, with a height of 0.67 meters, no sluice, and a diameter of 0.0625 meters. The lowest water outflow was discovered at a head of 0.55 meters with a water debit of 0.01036. The third attempt, which featured a sluice opening with a diameter of 0.0625 meters and a height of 0.67 meters (head), used the most water power in the experiment. The testing yielded the following results: 75.13 watts of water power, 5.16 watts of generator power, 0.233 N.m. of torque, 2.63 watts of turbine power with a generator load 3.73 watts without one, and 6.87% efficiency. Data gathered from the hydropower prototype's operation can be used to construct testing instruments for use in laboratories